Ontologisk urenhed i Gammel Testamente - Jensen, Hans J. Lundager (Religionsvidenskabeligt Tidsskrift, 1997)
The article discusses the rationality behind the category ontological (or natural) impurity in the priestly parts of the Pentateuch in the Hebrew Bible. After a discussion of Mary Douglas' hypothesis from 1966, correctly rejected by Jacob Milgrom, and a semiotic reformulation of Milgrom's definition of holy/common and unclean/clean, the thesis of Milgrom and others, according to which impurity basically signifies "death", is likewise rejected. As an alternative it is proposed that the basic difference between holiness and impurity consists in the difference between durative (transcendent) and periodic (human, terrestrial) life. This hypothesis meets Claude Lévi-Strauss' reflections on rationality of the taboo on menstruation in North American and other cultures; in both cases the rules of good behavious are based on a reluctance on the side of human beings towards the material world (in the Hebrew Bible garanted by Yahweh), the good periodicity of which should be protected against the powers inherent in the human bodies.